Ethics Commerce and Justice Understanding Al- Ghazali's Views on Economics and Business - Dita Rosyalita; Hagi Andhika; Iik Juniartinur; Amin Basir; Popon Srisusilawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines Imam Al-Ghazali's thoughts on economics and business ethics from an Islamic perspective. Using a qualitative approach based on literature, this study analyzes Al-Ghazali's main works such as Ihya ' Ulumuddin , al- Mustashfa , and relevant secondary literature. The results of the study indicate that Al-Ghazali emphasized the close relationship between economic activities and spiritual and moral values, where business is not only a means of obtaining worldly profits, but also an investment in the afterlife. He highlighted the concepts of maslahah , maqashid al- shari'ah , the hierarchy of human needs, social justice, and ethical principles in trade. Additionally, Al-Ghazali outlined the limits of profit, the the importance of wealth distribution, the prohibition of fraudulent practices, and the role of the state in creating a fair market. Al-Ghazali's thoughts have proven relevant to the challenges of the modern economy, particularly in building an ethical, sustainable, and welfare-oriented business system.